Exploring Arab and Western visitors' interpretive experiences at an Omani heritage site: does one size fit all?. Issue 2 (3rd March 2020) - Almuhrzi, Hamed; Hughes, Karen; Ballantyne, Roy
ABSTRACT: Heritage interpretation aims to enhance visitors' appreciation and understanding of cultural events, customs and peoples. Increasingly, heritage sites are attracting culturally diverse audiences with a range of expectations, needs and perceptions. Accordingly, researchers argue that streamlined interpretation that accommodates these differences may be needed. This study uses self-administered pre- and post-visit questionnaires to investigate the expectations and experiences of 612 Arab and Western visitors at Nizwa Fort, Oman. Arab visitors ('insiders') expressed a preference for interpretation that focused on their ancestors' achievements. They sought an emotional connection with the site and were particularly interested in oral interpretation. Western visitors ('outsiders') wanted explanations of Arab traditions, customs and history – essentially, they sought to place the heritage site within a cultural context. Findings provide insights into designing interpretation that caters for 'insiders' versus 'outsiders', particularly within a Middle Eastern context.